2016
DOI: 10.1080/0142159x.2016.1254757
|View full text |Cite
|
Sign up to set email alerts
|

Room for improvement: Palliating the ego in feedback-resistant medical students

Abstract: Feedback in medical education provides the impetus for growth in a field pressured to demonstrate continuous progress. Unfortunately, as it always incorporates some level of judgment, certain students appear more resistant than receptive to receiving feedback. Coupled with the ubiquitous stressors of medicine-examinations, perpetual knowledge acquisition, competition for employment-there subtly emerges a learning environment in which the mindset of medical trainees morphs from collegiality to outperformance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…On the contrary, several investigations exploring the correlation between the utilization of social networking and self-confidence have found that individuals who devote more time engaging with social networking platforms tend to exhibit lower levels of self-confidence (Hawi & Samaha, 2017 ; Vogel et al, 2015 ). This contradiction may be due to students receiving positive feedback, likes, or supportive comments on their posts or achievements on social media; it can increase their self-confidence by providing a sense of recognition and validation from their colleagues (Chretien et al, 2015 ; Perrella, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, several investigations exploring the correlation between the utilization of social networking and self-confidence have found that individuals who devote more time engaging with social networking platforms tend to exhibit lower levels of self-confidence (Hawi & Samaha, 2017 ; Vogel et al, 2015 ). This contradiction may be due to students receiving positive feedback, likes, or supportive comments on their posts or achievements on social media; it can increase their self-confidence by providing a sense of recognition and validation from their colleagues (Chretien et al, 2015 ; Perrella, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although, there is some degree of judgment in formative evaluation,[ 32 ] because of the comparison made between an individual's performance and the desired performance, it is not comparable to the summative evaluation. As the judgment latent in evaluation encourages the feedback recipient toward resistance to protect him/herself from emotional harm,[ 32 ] the feedback from the summative evaluation is expectedly associated with greater resistance, especially when indicating one's undesirable performance. Some organizations consider a range of low- to high-stake evaluations instead of combining formative and summative evaluation functions or separating them completely.…”
Section: Discussionmentioning
confidence: 99%
“…A quick response focused only on the cultural points of the report by Davies and Mannion [8] is evidence of active interest in this topic within the broader academic community. Further, examination of widespread mistreatment of medical school students [9], questioning the high-stakes competition of medical school as a contribution to physician ego [10], the national bestselling discussion of patient autonomy by Dr. Atul Gawande, Being Mortal, and the efforts of The Center for Open Science to create an unbiased, open model for the betterment of scientific information all emphatically point to multi-field interest in healthcare-focused paradigm change.…”
Section: Informationmentioning
confidence: 99%